2008
DOI: 10.1063/1.2841064
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric nano-Fe3O4∕CoFe2O4∥PbZr0.53Ti0.47O3 composite

Abstract: A new magnetoelectric hybrid device composed of a nanoparticulate magnetostrictive iron oxide-cobalt ferrite film on a piezoelectric lead zirconic titanate crystal serving as both substrate and straining medium is described. Nano-Fe 3 O 4 / CoFe 2 O 4 particles, ranging from 5 to 42 nm, were prepared using a variation of the sol-gel method. A small electric field, 5 -10 kV cm −1 , applied at the coercive field of the nano-Fe 3 O 4 / CoFe 2 O 4 component modulates the film magnetization up to 10% of the saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Traditionally, piezoelectric effect is an effi cient way to convent motion to electricity, [ 85 ] which has been designed and cooperated in some real systems, such as fi lms or textured fi lms with preferential orientation, and provide fl exibility to obtain thick fi lms with large areas. [112][113][114][115][116][117][118][119][120] However, when the growth of oxide thin fi lms with high structural perfection and the ability to customize oxide layering down to the atomic layer level are demanded, the traditional chemical methods are not applicable. Alternatively, the vapor deposition techniques (e.g., PLD, MBE, and sputtering) have the ability of yielding excellent epitaxial growth of thin fi lms with atomicscale thickness control and coherent interfaces.…”
Section: Energy Harvester and Conversion Devicesmentioning
confidence: 99%
“…Traditionally, piezoelectric effect is an effi cient way to convent motion to electricity, [ 85 ] which has been designed and cooperated in some real systems, such as fi lms or textured fi lms with preferential orientation, and provide fl exibility to obtain thick fi lms with large areas. [112][113][114][115][116][117][118][119][120] However, when the growth of oxide thin fi lms with high structural perfection and the ability to customize oxide layering down to the atomic layer level are demanded, the traditional chemical methods are not applicable. Alternatively, the vapor deposition techniques (e.g., PLD, MBE, and sputtering) have the ability of yielding excellent epitaxial growth of thin fi lms with atomicscale thickness control and coherent interfaces.…”
Section: Energy Harvester and Conversion Devicesmentioning
confidence: 99%
“…The electronic phase transition driven by strain under electric field is supported by works using LSMO, [17,18] LCMO, [39] and Pr 0.6 Ca 0.4 MnO 3 [40] with strong tendency toward phase separation as ferromagnetic layer. On the contrary, the changes of magnetic anisotropy under electric field was widely accepted in CoFe 2 O 4 [41,42] and Fe 3 O 4 , [43][44][45] where a magnetization orientation shift of 17° in Fe 3 O 4 /BaTiO 3 was observed.…”
Section: Ferromagnetic Oxidesmentioning
confidence: 99%
“…BTO, PMN-PT, and PZT). [17,18,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] The external electric field alters the lattice or shape of the ferroelectric crystal by the converse piezoelectric effect, and then transfers the strain to the proximate magnetic layer, leading to the changes in magnetic anisotropy, magnetization rotation, and coercivity through the magnetostriction. In the FM/FE heterostructures, both (anti-)ferromagnetic oxides and metals are controlled by electric field.…”
Section: Strain-mediated Electrical Control Of Magnetismmentioning
confidence: 99%
“…[4][5][6] We used this approach to improve on previous eutectoid 7 and other [8][9][10][11] syntheses of CFO/BTO composites. Avellaneda and Harshe 12 already demonstrated that solidification of eutectic BTO-CFO leads to lamellar microstructures.…”
mentioning
confidence: 99%